EKSPLORASI MAKNA PENGELOLAAN KEUANGAN: STUDI FENOMENOLOGI PADA MAHASISWA AKUNTANSI GENERASI Z - Mongan, Frischa Faradilla Arwinda; Claudio Julio Mongan; Olivya Vivien Lili Palamba; Siti Rahmadani R (Al-Buhuts, 2024)
This study aims to explore further what financial management means to accounting students in Generation Z. This generation is considered to have a consumer lifestyle due to the YOLO and FOMO mindset, especially for students who have acquired knowledge about accounting and finance. Qualitative methodologies are used in this kind of research. Exploring the meaning of financial management from the perspectives of all informants is based on phenomenology. The informants in this research are Generation Z accounting students. The results showed three meanings of financial management implied by each informant. Financial management means self-control, the scale of priorities, and the difference between being and not being